150k views
5 votes
If f(x)=5x-4 and g(x)=4x+1, find (f-g)

If f(x)=5x-4 and g(x)=4x+1, find (f-g)-example-1

1 Answer

2 votes

Answer:

B

Explanation:

What this tells you is to take 4x + 1 away from 5x - 4

Givens

f(x) = 5x - 4

g(x) = 4x + 1

Formula

(f - g)(x)

Solution

(f - g)x = 5x - 4 - (4x + 1) remove the brackets

(f - g)x = 5x - 4 - 4x - 1 Collect like terms

(f - g)x = 5x - 4x - 4 - 1

(f - g)x = x - 5

Answer

B

User Ajay Datla
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.